Cyber-Physical System (CPS): State of the Art - Juliza Jamaludin; Rohani, JM (IEEE, 2024)
Cyber-Physical System (CPS) plays an important role in today's cyber world. Without the existence of the advancements of CPS technologies and knowledge's, we will having difficulties for long distance control and communications. Most of the recent research are discussing on the external threat to the CPS. The external threat will affect the industries and surveillance. Our routine may disturbed by a single cyber-attack to the CPS network at it will caused a loss of money and damages. This review paper discussed in details on the state of the art of CPS. The two main criteria of CPS which being discussed in this review paper are, CPS characteristic and CPS architectures. Deep studies on CPS characteristic and architectures are important to understand its functionality and to identify the weakness of the system. More research need to be conducted on CPS security and performance due to the extensive growing of the 4th industrial revolution.